Evaluation of the shear bond strength of two resin cements on different CAD/CAM materials. Issue 9 (2nd May 2016) - Secilmis, Asli; Ustun, Ozlem; Kecik Buyukhatipoglu, Isil
Abstract: Objective: This study investigated the bond strength of two resin cements (Panavia F 2.0 and Multilink N) to different CAD/CAM materials: resin nanoceramic (RNC; Lava Ultimate), hybrid ceramic (HC; Vita Enamic), zirconia-reinforced lithium silicate ceramic (ZLDC; Vita Suprinity), and lithium disilicate glass-ceramic (LDG; IPS e.max CAD HT). Material and methods: CAD/CAM blocks of 2-mm thickness were sectioned with a slow-speed diamond-saw sectioning machine. The slabs were then embedded in autopolymerizing acrylic resin ( n  = 12), and resin cements were applied to the surface of the specimens. All specimens were stored in water for 24 h and subjected to 5000 thermal cycles. Bond strength was measured by means of the shear bond strength test. The data were statistically analyzed by two-way ANOVA and Tukey LSD post hoc tests. Results: The results of the two-way ANOVA test indicated that the bond strength values varied significantly depending on the CAD/CAM restorative materials, resin cements, and interaction of these variables ( p  < 0.05). The RNC group showed the highest bond strength for Panavia F 2.0 ( p  < 0.05); there were no significant differences among other CAD/CAM materials for Panavia F 2.0 ( p  > 0.05). The LDG group showed the highest bond strength for Multilink N, it was followed by the ZLDC group ( p  < 0.05); there were no significant differences between RNC and HC groups ( p  > 0.05). Conclusions: Choosing resin cements for restorations should be done carefully because bond strength values vary significantly depending on the resin cement and CAD/CAM restorative material.